15-Deoxy-Δ(12,14) Prostaglandin J(2) Reduces the Formation of Atherosclerotic Lesions in Apolipoprotein E Knockout Mice - Seno, Takahiro (Public Library of Science, 2011)
AIM: 15-Deoxy-Δ(12,14) Prostaglandin J(2) (15d-PGJ(2)) is a ligand of peroxisome proliferator-activated receptor γ (PPARγ) having diverse effects such as the differentiation of adipocytes and atherosclerotic lesion formation. 15d-PGJ(2) can also regulate the expression of inflammatory mediators on immune cells independent of PPARγ. We investigated the antiatherogenic effect of 15d-PGJ(2). METHODS: We fed apolipoprotein (apo) E-deficient female mice a Western-type diet from 8 to 16 wk of age and administered 1 mg/kg/day 15d-PGJ(2) intraperitoneally. We measured atherosclerotic lesions at the aortic root, and examined the expression of macrophage and inflammatory atherosclerotic molecules by immunohistochemical and real-time PCR in the lesion. RESULTS: Atherosclerotic lesion formation was reduced in apo E-null mice treated with 15d-PGJ(2), as compared to in the controls. Immunohistochemical and real-time PCR analyses showed that the expression of MCP-1, TNF-α, and MMP-9 in atherosclerotic lesions was significantly decreased in 15d-PGJ(2) treated mice. The 15d-PGJ(2) also reduced the expression of macrophages and RelA mRNA in atherosclerotic lesions. CONCLUSION: This is the first report 15d-PGJ(2), a natural PPARγ agonist, can improve atherosclerotic lesions in vivo. 15d-PGJ(2) may be a beneficial therapeutic agent for atherosclerosis.